Echoes of the past: The enduring impact of communism on contemporary freedom of speech values - Milena Nikolova; Olga Popova (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper studies the long-term consequences of communism on present-day freedom of expression values in two settings - East Germany and the states linked to the sphere of influence of the former USSR. Exploiting the natural experiment of German separation and later reunification, we show that living under communism has had lasting effects on free speech opinions. While free speech salience has increased for East and West Germans vis-à-vis other government goals, the convergence process has been slow. East Germans are still less likely to consider freedom of speech a key government priority compared to West Germans. Additionally, our analyses of secret police surveillance data from East Germany point to the fact that geographybased measures of community experiences of past political repression do not explain our findings. The same conclusion holds when we look at the setting of the former Soviet Union and we correlate proximity to Stalin's former labor camps in the Soviet Union with present-day freedom of speech values. At the same time, family experiences with political repression in Eastern Europe/the former Soviet Union exert a discernible influence on current values towards freedom of speech, likely due to a lasting impact stemming from such personal encounters. As such, our paper adds a nuanced contribution to the economics of free speech, suggesting that freedom of speech may be a part of informal institutions and slow-changing cultural values.
Keywords: D02; N00; P27; P52; 330; political repression; communism; free speech; German Democratic Republic; EasternEurope; former Soviet Union; economic history